2007
DOI: 10.1099/vir.0.82990-0
|View full text |Cite
|
Sign up to set email alerts
|

The cysteine protease inhibitors cystatins inhibit herpes simplex virus type 1-induced apoptosis and virus yield in HEp-2 cells

Abstract: The role of cystatins in herpes simplex virus (HSV)-induced apoptosis and viral replication has been studied. Human epithelial (HEp-2) cells infected with wild-type HSV-1 (F), with a deletion virus lacking the anti-apoptotic gene Us3 (R7041) or with a deletion virus lacking the anti-apoptotic genes Us3 and ICP4 (d120) were treated with cystatin A, C or D. Cells and culture media were studied at different time points for replicating HSV-1 and for apoptosis. Cystatins C and D inhibited the yield of replicative H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…Exogenously added cystatin A suppressed propagation of HSV-1 as reported previously (24), which suggested that it internalized into FL cells (Fig. 5).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Exogenously added cystatin A suppressed propagation of HSV-1 as reported previously (24), which suggested that it internalized into FL cells (Fig. 5).…”
Section: Discussionsupporting
confidence: 48%
“…A serine protease inhibitor prevents the release of viral DNA from the capsid and suppresses HSV-1 replication. Peri et al reported that cystatins partially inhibit HSV-1 propagation (24). They speculated that the ubiquitin-specific cysteine protease UL36 USP , which is an N-terminal fragment generated by proteolytic cleavage of pUL36 of HSV-1, is a target for cystatins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several viral proteins such as Nef from human immunodeficiency virus-1, protein U7 from human papillomavirus type-16, parvovirus H1 and herpes simplex virus infection induce LMP-and cathepsin-dependent cell death (Kaznelson et al, 2004;Di Piazza et al, 2007;Laforge et al, 2007). Cystatin C can block the enhanced CB activity observed in herpes simplex virus type-1-infected cells and concomitantly inhibits herpes simplex virus type-1 replication and host cell apoptosis (Peri et al, 2007). The protein E7 encoded by human papillomavirus type-16 can induce caspase-dependent apoptosis in different cell lines.…”
Section: Inducers Of Lmpmentioning
confidence: 99%
“…CTS3 is a secreted cysteine protease inhibitor extensively distributed in the extracellular matrix. It functions in the regulation of apoptosis and exert inhibitory effects against viral replication and RNA virus induced apoptosis [31, 32]. The observed decrease in abundance of CTS3, together with the cathepsins, may have an effect in promoting CHIKV dissemination.…”
Section: Discussionmentioning
confidence: 99%